2022
DOI: 10.1002/slct.202201992
|View full text |Cite
|
Sign up to set email alerts
|

A Bienzymatic Cascade for the Complete Hydrolysis of Phthalic Acid Esters

Abstract: Phthalic acid esters (PAEs) are widely used as plastic additives to increase the flexibility and durability of plastics. Constantly leaching out from plastics, PAEs are ubiquitously found in the environment. As PAEs exhibit biological activities such as being endocrine disruptive, the quest for efficient degradation strategies continues. Here, we report a bienzymatic degradation system for PAEs to phthalic acid (PA) using a cascade comprising two hydrolases, EstJ6 and P8219. The reaction conditions were optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Among these techniques, the washing condition involves washing phosphogypsum with three times the amount of tap water 3-4 times until the washing liquid is neutral; the condition of lime neutralization involves adding lime to phosphogypsum with a water content of about 15%, mixing well, and then aging for 24 h. Li et al [84] indicated that the content of soluble fluorine in phosphogypsum is reduced from 0.02% to 0.014% after aging with 0.4% lime for 12 h. They showed that through the use of 30% sulfuric acid, with a liquid/solid ratio of 3 mL/g, a temperature of 55 • C, and acid leaching for 120 min, the total fluorine content in phosphogypsum can be reduced from 0.18% to 0.016%. Yang [77] indicated that with 30-35% sulfuric acid leaching at 90 • C, the total fluorine content in phosphogypsum can be reduced from 0.23% to 0.06%.…”
Section: Fluoride Impurity Removalmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these techniques, the washing condition involves washing phosphogypsum with three times the amount of tap water 3-4 times until the washing liquid is neutral; the condition of lime neutralization involves adding lime to phosphogypsum with a water content of about 15%, mixing well, and then aging for 24 h. Li et al [84] indicated that the content of soluble fluorine in phosphogypsum is reduced from 0.02% to 0.014% after aging with 0.4% lime for 12 h. They showed that through the use of 30% sulfuric acid, with a liquid/solid ratio of 3 mL/g, a temperature of 55 • C, and acid leaching for 120 min, the total fluorine content in phosphogypsum can be reduced from 0.18% to 0.016%. Yang [77] indicated that with 30-35% sulfuric acid leaching at 90 • C, the total fluorine content in phosphogypsum can be reduced from 0.23% to 0.06%.…”
Section: Fluoride Impurity Removalmentioning
confidence: 99%
“…Yang [77] treated phosphogypsum using a single impurity removal technique (acid leaching) and investigated the removal of iron impurities. He found that the ferric oxide content in phosphogypsum can be reduced from 0.28% to 0.21% by using 30-35% sulfuric acid and acid leaching at 90 • C.…”
Section: Iron Impurity Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…Biocatalysis has had a profound impact on chemical synthesis, offering environmental benefits and the ability to achieve high product yields and enantiomeric excesses through streamlined synthetic routes. 1–10 Over the past decades, the scope of enzymatic applications in non-natural reactions has significantly expanded, thereby broadening their utility in chemical synthesis. 11–31 Hemoproteins, including cytochrome, peroxidase, myoglobin, and hemoglobin, have demonstrated the ability to mediate carbene-type C–C bond formations such as cyclopropanation, C–H insertion and ylide formation.…”
Section: Introductionmentioning
confidence: 99%